Hakikat Dan Prinsip Metode Pembelajaran Pendidikan Agama Islam - Arlina Arlina; Jeni Anwar Rambe; Muhammad Zailani; Rani Wardani Hasibuan; Nadya salsabilah; Rizka Ardianti (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The method is very important in facilitating a job because the method is a systemic way of working to facilitate the implementation of an activity in order to achieve the specified goals. The Islamic Religion Learning Method itself certainly cannot be separated from the main objectives of religious education in Indonesia which are listed in article 39 paragraph 2 of Law no. 20 of 2003,